Taste-Characteristic Attributes and Related Contribution Compounds of White Tea - Yilin TONG; Fangyuan FAN; Yuqian TIAN; Shuying GONG; Haowei GUO; Chuangsheng HUANG; Senjie ZHOU (Shipin gongye ke-ji, 2022)
This study focused on the taste-characteristic attributes of representative white teas and related taste-chemical compositions. In this study, the white tea made from 9 representive cultivars were taken as research objects, including Fuding Dabaicha, Fuan Dabaicha, Chun Yu2 etc. Sensory evaluation according to the national standard was used for taste-characteristic attributes analysis, high-performance liquid chromatography(HPLC) and other techniques were used for chemical detection, and chemometrics analysis was used to explore the relationship between taste-characteristic attributes and chemical compositions. In this study, 9 types of white teas of different cultivars reflected six main taste-characteristic attributes: Clear, fresh, sweet, mellow, thick, and strong. Glutamic acid was correlated with the umami taste attribute in white tea samples(R=0.525) positively. The fresh taste was positive correlated with ratio of glutamate to the sum of epigallocatechin gallate and epigallocatechin(Glu/(EGCG+EGC)) strongly(R=0.695). And the ratio of total kaempferide to total flavonol glycoside(Kae/TFOG) was positively correlated with the fresh taste(R=0.452). Meanwhile, the high ratio of total amino acids to total catechins(aa/Ca>0.30) and ratio of total amino acids to total alkaloids(aa/Alk>0.90) contributing to the mellow and thick taste in the samples greatly.